Integrated multiomics of pressure overload in the human heart prioritizes targets relevant to heart failure - Brian R. Lindman; Andrew S. Perry; Michelle L. Lance; Kaushik Amancherla; Namju Kim; Quanhu Sheng; Phillip Lin; Ryan D. Pfeiffer; Eric Farber-Eger; William F. Fearon; Samir Kapadia; Dharam J. Kumbhani; et al. (Nature Communications)
Abstract Pressure overload initiates a series of alterations in the human heart that predate macroscopic organ-level remodeling and downstream heart failure. We study aortic stenosis through integrated proteomic, tissue transcriptomic, and genetic methods to prioritize targets causal in human heart failure. First, we identify the circulating proteome of cardiac remodeling in aortic stenosis, specifying known and previously-unknown mediators of fibrosis, hypertrophy, and oxidative stress, several associated with interstitial fibrosis in a separate cohort (N = 145). These signatures are strongly related to clinical outcomes in aortic stenosis (N = 802) and in broader at-risk populations in the UK Biobank (N = 36,668). We next map this remodeling proteome to myocardial transcription in patients with and without aortic stenosis through single-nuclear transcriptomics, observing broad differential expression of genes encoding this remodeling proteome, featuring fibrosis pathways and metabolic-inflammatory signaling. Finally, integrating our circulating and tissue-specific results with modern genetic approaches, we implicate several targets as causal in heart failure.